2012
DOI: 10.1149/2.004302jss
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Chemistry Derived Advanced Phosphors for Smart Lighting Devices Based on Blue or UV LEDs

Abstract: This work deals with phosphors suitable for applications in a new generation of Hg-free lamps based on deep ultraviolet (DUV), ultraviolet (UV) and blue light emitting diodes (LEDs). First, two synthesis routes, solid state reaction and Pechini method, have been used for preparing an original red phosphor, Y 3 BO 6 :Eu 3+ . Phase purity was confirmed by XRD analysis for Pechini derived sample after washing the powder with an acidic solution while the synthesis dependence of the morphological and optical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…RE 3 BO 6 is an important host for luminescence applications, and it always crystallizes in three different space groups, including P 2 1 / c (RE = La‐Nd) and C 2/ m , C 2, or C m (RE = Pm‐Yb, Y) . Comparing with REBO 3 and REB 3 O 6 , RE 3 BO 6 is the rare earth rich host with RE 3+ occupying a low‐symmetry site, which has aroused a considerable interest in recent years . For example, red emission intensity from Eu 3+ is much stronger when doped in Y 3 BO 6 lattice compared to YBO 3 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…RE 3 BO 6 is an important host for luminescence applications, and it always crystallizes in three different space groups, including P 2 1 / c (RE = La‐Nd) and C 2/ m , C 2, or C m (RE = Pm‐Yb, Y) . Comparing with REBO 3 and REB 3 O 6 , RE 3 BO 6 is the rare earth rich host with RE 3+ occupying a low‐symmetry site, which has aroused a considerable interest in recent years . For example, red emission intensity from Eu 3+ is much stronger when doped in Y 3 BO 6 lattice compared to YBO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Pradal et al reported that the Eu 3+ content in Y 3 BO 6 can be up to 20 mol%, and the Y 3 BO 6 :Eu‐PVP composites exhibited the characteristic red emission of Eu 3+ rather than orange‐red under UV light excitation, indicating that they are potential candidates for next generation white light emitting diodes (LEDs) . However, it is noticed that rare‐earth borates including RE 3 BO 6 were usually synthesized by typical solid‐state reactions at high temperatures or sol‐gel technology followed by calcination . Therefore, the final products are always characterized by large size, irregular shape, and significant aggregation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations